Understanding police interrogation : confessions and consequences - Woody, William Douglas; Forrest, Krista D. (Psychology and crime series., 2020)
What drives suspects to confess during police interrogation? In particular, why do some people falsely confess to serious crimes, despite both the likelihood of severe negative consequences and their actual innocence? Too often, observers endorse the mistaken belief that only people with severe mental illnesses or cognitive disabilities would confess falsely. This common but erroneous belief overlooks the risks that result from additional factors that can influence the nature of an interrogation and may conduce to a false confession, including investigators' biases, cultural views about race and crime, the powerful effects of police deception on suspects, and characteristics of the suspect and of the circumstances that can increase the suspect's vulnerability. This book examines numerous cases of false confession to clarify the totality of the circumstances surrounding interrogation and confession.